Where My Heart Belongs - Amelia Hartanta (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Teen drama films, which usually consist of “finding self-identity”, usually talk about how the teenagers survive, trying to fit in the society so they can be accepted as another identity. My creative work is abouta girl who has been compared by her mother to her sister since her childhood and also being bullied because she does not have good grades, thus leads her to grow into a ball of inferiority and lose herself. She goes on a journey with her punk friends to find her father and finally, she finds her true self. The main subject matter for this creative work is self-identity. However, the theme is how social environment can make people feel inferior and shape someone’s identity. The theory used for this work is ‘Stages of Psychosocial Development’ by Erik Erikson. This theory helps to find the crisis inside a specific range of ages when the stage is not met.